How Technology Has Affected Communication? - Musulmonova Shokhruza Mukhtorjon Daughter; To'lkinova Okhista (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
The evolution of technology has had a transformative impact on communication, revolutionizing the ways in which individuals and organizations exchange information. This paper explores the multifaceted effects of technological advancements on communication, including increased speed and accessibility, the rise of social media and digital platforms, and changes in communication styles. It also addresses concerns about the quality of interpersonal relationships, privacy and security challenges, and the future implications of emerging technologies such as artificial intelligence and virtual reality. Through a comprehensive analysis, this paper highlights the profound role technology plays in shaping both personal and professional communication, and suggests pathways for balancing its advantages and drawbacks.